Citizenship law, nationalism and the theft of enjoyment: a post-colonial narrative - Roshan De Silva Wijeyeratne (Law Text Culture, 1998)
My focus here is on the debates and law on citizenship in Sri Lanka. I shall consider the extent to which The Ceylon Citizenship Act, 1948 (which restricted the status of Ceylon citizen to anyone who could claim it by descent or registration and as a result disenfranchised a large proportion of the 700,000 Indian Tamil plantation workforce), fails to establish a self-constituting foundation for the granting of citizenship. I go on to suggest that such legislation can only function by virtue of the (im)possibility of excluding the Tamil other, that is the problem of locating the other. This im)possibility, I shall argue is another name for Derridean differance, the other never absolutely excluded, but never absolutely included either, within the textual framework ofthis legislation. The inherent anxiety ofthe relation between the demarcation of citizenship for the Sinhalese and citizenship for the Indian Tamils is elaborated upon in a discussion that draws on Zizek's (1991 a, 1993) psychoanalytical account of nationalism/national identification as the 'theft of enjoyment'. Just as the Sinhalese Buddhist nation exhibits an anxious moment that unsettles the certainty ofthe relation between the Sinhalese and the Tamil other, the other whose proximity undermines the possibility of national coherance and consistency, The Crylon Citizenship Actand its derivative legislation similarly experiences this problem of 'placing' the Indian Tamil other. As with the following discussion of the limit of Sinhalese Buddhist nationalism, my emphasis with reference to the law on citizenship is with an alterity that can never be absolutely excluded. But first I shall elaborate upon Derridas concept ofdifferance.